TRANSFORMATION OF INDONESIAN SEA TRANSPORTATION AND MARITIME LOGISTICS TO REALIZE THE VISION OF GOLDEN INDONESIA 2045 - K.P.Suharyono S.Hadiningrat; Bahana Wiradanti; Yusuf Ferdian Umar (JIPOWER : Journal of Intellectual Power, 2024)
As a large archipelago country, Indonesia envisions to become a "Sovereign, Advanced, and Sustainable Archipelago Country" by 2045. All sectors are making efforts to make this vision reality, including its maritime transport sector. Significant transformations in maritime transportation and logistics are essential. Despite maritime logistics not being explicitly mentioned in the 2025-2045 Long Term Development Plan, the paper highlights its critical roles, such as linking islands, improving port infrastructure, supporting trade, and enhancing logistics connectivity. One of the key transformations discussed in the paper is the merger of PT Pelabuhan Indonesia (Persero), which aims to streamline port operations and integrate port facilities to boost efficiency and competitiveness. Additionally, the paper underscores the importance of the blue economy, which involves sustainable marine management and conservation to drive economic growth. The blue economy's principles, such as resource efficiency, minimizing waste, and fostering social inclusion, are crucial for achieving sustainable development. Indonesia's active participation in the Archipelagic and Island States (AIS) Forum is also highlighted as a vital platform for collaboration among island nations to tackle global maritime issues. The forum's focus on climate change, disaster management, blue economy, and maritime governance aligns with Indonesia's goals to leverage its maritime potential for national prosperity. Lastly, the paper also stresses the importance of adhering to Environment, Sustainability, and Governance (ESG) aspects in maritime logistics. Continuous improvement in these areas, alongside active communication with stakeholders and international bodies like the World Bank and UNCTAD, is necessary to support policy formulation and enhance Indonesia's logistics performance. In conclusion, the transformation of Indonesia's maritime sector involves robust port infrastructure, blue economy initiatives, and active global collaboration through the AIS Forum. These efforts are geared towards achieving the Vision of Golden Indonesia 2045, ensuring sustainable growth and prosperity for the nation. Furthermore, the paper contributes to research and policy recommendations for archipelago countries around the globe.